Nutritional impact study of the income generation for vulnerable group development program: report of January 1995 - Hyder, S.M. Ziauddin (BRAC Research and Evaluation Division (RED), 2019)
This report is a part of the longitudinal study titled "Nutritional Impact study of the Income Generation for the Vulnerable Group Development Programme'' launched in Tangail district in January 1993. The data has been collected every six months on a cohort of population. Data for this study was collected in January 1995 on the three types of the study population: lGVGDP participants, non-lGVGDP from within the programme area and non-lGVGDP from outside the programme area. The study compares nutritional and other socioeconomic variables between the population groups to assess impact of the programme on nutritional status of the target populations. lt may be concluded from the study that the programme could bring about positive impact on pre-school children's nutritional status through increasing socio-economic and hygiene status of the programme participating households.